Comparative effectiveness of two first-line, ICI-based regimens for advanced HCC: a target trial emulation using an electronic medical record network - Shiraishi, Chihiro; Shigyou, Miho; Inoue, Ryuichi; Ogura, Toru; Kaneshige, Susumu; Hayashi, Toshinobu (Frontiers in Oncology, 2026)
IntroductionHead-to-head comparative evidence of the relative efficacies of atezolizumab plus bevacizumab (Atezo+Bev) and tremelimumab plus durvalumab (Treme+Dur) as first-line therapies for advanced hepatocellular carcinoma (HCC) remains limited. Thus, in the present study, we compared the real-world efficacy and safety of these two modalities using a target trial emulation approach.MethodsUsing the TriNetX Research Network, we identified adults (≥20 years) with HCC (ICD-10 C22.0) who initiated first-line Atezo+Bev or Treme+Dur (November 2022– November 2024). Propensity score matching (1:1) was used to balance the baseline characteristics. The primary outcome measure was overall survival (OS). Secondary outcomes included 1- or 2-year OS and organ-specific immune-related adverse events (irAEs) within 12 months, based on pre-specified ICD-10 definitions.ResultsAfter matching, 640 patients were included in each group. Residual imbalance persisted in hepatic reserve markers (albumin, international normalized ratio, and platelet count; standardized mean differences >0.1). One-year OS was numerically higher in the Atezo+Bev group than in the Treme+Dur group (61% vs 55%; hazard ratio [HR], 0.806; 95% confidence interval [CI], 0.665–0.976; p = 0.027). Two-year OS (HR, 0.864; 95% CI, 0.723–1.031; p = 0.105) and overall OS showed no significant differences (median: 19.4 vs 19.0 months [591 vs 578 days]; HR, 0.886; 95% CI, 0.743–1.057; p = 0.179). Most irAEs were similar; however, the time-to-first hepatic irAEs favored Atezo+Bev (HR, 0.678; 95% CI, 0.487–0.943; p = 0.020). Notably, respiratory irAEs occurred significantly earlier in the Treme+Dur group than in the Atezo+Bev group (mean onset: 2.4 vs 3.2 days; p = 0.031).ConclusionsIn this real-world target trial emulation, Atezo+Bev and Treme+Dur demonstrated broadly comparable long-term OS rates when used as first-line therapies for HCC. While baseline hepatic reserve plays an important role, the treatment regimen itself may contribute to earlier onset of hepatic and respiratory irAE. Careful monitoring for early-onset hepatic dysfunction and respiratory irAEs may be warranted in patients treated with Treme+Dur combination therapy.